Hydrological and erosional dynamics: responses to changes in land uses and climate in the Cerrado biome - Schwamback, Dimaghi (2024)
The Brazilian Cerrado is the major national epicenter for agricultural production and a main contributor to the Brazilian economy. Thus, the biome faces increasing pressure from agricultural expansion that alters local and regional hydrological processes (infiltration, runoff, evapotranspiration, soil loss). There is a lack of understanding how these processes will respond to climate change. Consequently, this thesis investigates the intricate interplay between land cover and land use (LCLU) patterns and climate change on soil loss and on the dynamics of water balance components (surface flux, evaporation, soil-water storage, infiltration, groundwater flux, and root uptake) in a study area within the Cerrado biome. Using a multidisciplinary approach, surface runoff, soil losses and meteorological parameters were measured in experimental plots (100 m2 and 9% slope) during 10 years. The plots contained five typical LCLU in Brazil (sugarcane, pasture, Cerrado, soybean, and bare soil). Besides using standard equipment, two novel innovations for the design and construction of low-cost equipment for real-time measurements of surface runoff and soil water content were proposed. Based on the experimental data, we calibrated consolidated models for soil loss (Universal Soil Loss Equation - USLE) and subsurface water movement (Hydrus). Subsequently, we coupled the models to SSP2-4.5 and SSP5-8.5 future scenarios of climate model projections from the last generation (CMIP6) to predict the intermediate (2040-2070) and distant future (2071-2100) climate impact on hydrodynamics processes. The effects of climate change may lead to an increase of up to 4.9% (SSP2-4.5 scenario) and 7.6% (SSP5-8.5 scenario) of soil loss for all LCLU up to the end of the century. The climate change effects on water balance components are larger, with an increase of up to 28% in root water uptake for sugarcane areas (SSP5-8.5 scenario) by the end of the century. By assessing the interactions between land use, climate variability, and hydrological and erosion processes, this thesis informs decision-makers and stakeholders about the critical need for proactive conservation and adaptation measures in the face of ongoing environmental changes in the Cerrado ecosystem.